Pengaruh Penerapan Media Spinning Wheel Terhadap Hasil Belajar PAI Kelas VII SMP Negeri 7 Bukittinggi - Nofita, Elsa; Kamal, Muhiddinur; C, Charles; Wati, Salmi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
When studying, students do more than just sit back and listen to the instructor's words. Active involvement in the learning process is also expected from students. Student engagement, teacher-student communication, and overall enthusiasm for Islamic religious education can all benefit from the use of Spinning Wheel media. Student engagement, teacher-student communication, and overall enthusiasm for Islamic religious education can all benefit from the use of Spinning Wheel media. The main aim of this research is to determine the impact of using Spinning Wheel media on the learning outcomes of class VII students. Bukittinggi, SMP Negeri 7, in the Islamic Religious Education class. Using a posttest-only control group design, this quantitative study employed a quasi-experimental methodology. The use of Spinning Wheel media is one of two independent factors in this research, while the results of learning activities are the dependent variable. The experimental group and control group each completed 16 multiple choice test questions to collect data. In this study, a random selection procedure was used to select 60 students from a population of 217. If the decision making value is less than 0.05, it means that the dependent and independent variables are significantly different. Because there is an influence of variations in the treatment of each variable, the sig value of the questions filled in by the control and experimental classes is 0.022. Therefore, it is natural to assume that class VII students of SMP Negeri 7 Bukittinggi benefit academically from using the Spinning Wheel media in their Islamic religious education classes.